2019
DOI: 10.3389/fped.2019.00192
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Brain Injury on Processing of Emotional Prosodies in Neonates

Abstract: Being able to appropriately process different emotional prosodies is an important cognitive ability normally present at birth. In this study, we used event-related potential (ERP) to assess whether brain injury impacts the ability to process different emotional prosodies (happy, fear, and neutral) in neonates; whether the ERP measure has potential value for the evaluation of neurodevelopmental outcome in later childhood. A total of 42 full-term neonates were recruited from the neonatology department of Peking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…When comparing the results of healthy and mild HIE neonates, we found a difference in their ability to recognize emotional prosodies in the right middle frontal gyrus area, especially when listening to the angry prosody. This implies that mild brain injury can affect the ability of neonates to differentiate among emotional prosodies, which is consistent with the findings of Sun et al (Sun et al., 2019). In our study, all neonates went through fNIRS examination within 24 hr of life, for neonates at high risk of brain injury, even those without typical clinical manifestations, we may still be able to use fNIRS to test their ability to differentiate among emotional prosodies to achieve early discovery, and hence, early treatment of mild brain injury.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…When comparing the results of healthy and mild HIE neonates, we found a difference in their ability to recognize emotional prosodies in the right middle frontal gyrus area, especially when listening to the angry prosody. This implies that mild brain injury can affect the ability of neonates to differentiate among emotional prosodies, which is consistent with the findings of Sun et al (Sun et al., 2019). In our study, all neonates went through fNIRS examination within 24 hr of life, for neonates at high risk of brain injury, even those without typical clinical manifestations, we may still be able to use fNIRS to test their ability to differentiate among emotional prosodies to achieve early discovery, and hence, early treatment of mild brain injury.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, it is necessary to find more modalities for early diagnosis to guide hypothermia treatment and improve prognosis. Compared to neonates with moderate to severe encephalopathy, the poor prognosis of neonates with mild brain injury is more likely to manifest as cognitive impairment (Decety & Howard, 2013), previous studies have shown that neonates with HIE have impaired ability to differentiate among emotional prosodies, which constitutes a crucial component of cognitive function (Sun et al., 2019). Therefore, the rationale of the present study was to examine whether it is possible to use changes in the ability to differentiate among emotions for the early diagnosis of mild brain injury in neonates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 This medication is frequently utilized to advance the animal breeding sector in addition to preventing and treating several ailments. [2][3][4] The overuse of this medication has led to a variety of residual issues in the environment and animal-derived foods. Due to antibiotics' ability to alter microbial structure and functions and have an impact on the emergence of antimicrobial resistance, the Rapid Alert System for Food and Feed (RASFF) of the European Union warns that even a small amount of antibiotic residue in edible animal parts may be harmful to the public's health.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng's research ( 19 ) shows that healthy full-term newborns produce different MMR amplitudes in response to different emotional prosodies (happy/fearful), and higher MMR amplitudes with negative (fearful) prosodies. Our previous study ( 20 ) showed that the MMR amplitude of neonates with brain injury decreased and was related to poor neurodevelopmental outcomes at 30 months ( 20 ). However, the previous study didn't analyze the relationship between MMR amplitude and the risk of ASD.…”
Section: Introductionmentioning
confidence: 99%